Trade policy issues and developments - Anjaria, Shailendra J.; Kirmani, Naheed; Petersen, Arne B. (Washington, D.C. : International Monetary Fund, 1985)
The book reviews recent developments in trade and outlines the main issues facing governments in the international trade policy field.
"July 1985."
Bibliography: p. 87-90.
gau 27/02/17
Loans
Keywords: Commercial policy